Overload of the lower limbs of firefighters as a result of external conditions - Dagmara Iwańska; Piotr Tabor; Czesław Urbanik; Ida Wiszomirska; Andrzej Mastalerz (PLoS ONE, 2025)
Background It is known that a firefighter’s uniform with all equipment will significantly increase the load on the lower limbs during landing. The higher landing height will also increase ground reaction forces. However, it is unknown what effect the firefighters’ experience (job seniority) will have on the load. Moreover, age-related changes in neuromuscular control, balance, and muscular strength may alter the way external loads are managed, potentially increasing susceptibility to overload. Objective The present study aimed to evaluate the overload of the musculoskeletal system resulting from changing external conditions. Methods The main study involved 171 firefighters divided into three age categories: up to 25 years (I n=83 ), up to 44 years (II n=38 ) and over 44 years (III n=50 ). The subjects performed three landing on to the force platforms from two heights (0.5 m; 1.0 m) and in two types of clothes: sport and fire protection. For the evaluation of lower limb overloads, the value of generated ground reaction force relative to body weight (GRF/BW) of the participant and time of force affecting the locomotor system (amortization time) were evaluated (t > 1 BW). Results Increasing the landing height from 0.5 m to 1 m resulted in a significant ( p < 0.001 ) increase in ground reaction forces. Furthermore, younger participants generated significantly greater forces ( p < 0.001 ). Performing the landing in protective clothing also resulted in increased load (p < 0.001). Furthermore, older firefighters had a longer ( p < 0.01 ) cushioning time at both landing heights and in both clothing. Conclusion and application These results suggest that younger or less experienced firefighters may employ suboptimal landing strategies, increasing their injury risk.